Epidemiological and clinical profiles of septic arthritis in children of 0-2 years of age in Eastern Uttar Pradesh, India - Ahmad, Ekbal; Singh, Priyanka; Pradhan, Pawan; Singh, Vijay Kumar; Sharma, Bhoopendra (International Journal of Contemporary Pediatrics, 2024)
Background: Septic arthritis identified as infectious arthritis is a serious joint infection following the invasion of joint cavities by infectious agents usually bacteria. Due to speediness of joint destruction untreated septic arthritis may result in morbidity and mortality. Methods: Out of 71 sick children attending pediatric OPD/IPD of BRDMC Gorakhpur with musculoskeletal infection during November 2019 to October 2020, 52 patients of 0-2 years of age were enrolled for study. The computerized charts containing various parameters related to the epidemiological and clinical profiles of the patients were recorded and analyzed following statistical package for the social sciences (SPSS) version 23. Results: Out of 52 children 28.8% were neonates under the age of 28 days, 73.1% were full-term infants and 23.1% were premature. Likewise, 17.3% of the cases were with low birth weight whereas 7.7% had a history of septic infection. Hip joints in 65.4%, knee joints in 23.1% and elbow and shoulder joints in 5.8% of patients were infected. 44.2% of cases had right side involvement, 36.5% left side, 19.2% e bilateral joints, 80.8% Mono-articular and 19.2% showed poly-articular involvement. 84.6% of cases showed joint pain whereas 92.3% showed joint swelling. In 20% patients microbial culture of joint fluid revealed the growth of Staphylococcus aureus, Candida spp, E. coli and Pseudomonas spp. In 78.8% cases no growth of any pathogen was recorded in their blood culture. Ultrasonography (USG) diagnosis revealed fluid collection at joints in 94.2% cases while 5.8% exhibited pus collection. Conclusions: Septic arthritis was more common in males than females, monoarticular involvement was more common on the right side, hip joints were most affected joints and Staphylococcus aureus was the most common pathogen affecting the patients.